2013
DOI: 10.1073/pnas.1302751110
|View full text |Cite
|
Sign up to set email alerts
|

Number sense in infancy predicts mathematical abilities in childhood

Abstract: Human infants in the first year of life possess an intuitive sense of number. This preverbal number sense may serve as a developmental building block for the uniquely human capacity for mathematics. In support of this idea, several studies have demonstrated that nonverbal number sense is correlated with mathematical abilities in children and adults. However, there has been no direct evidence that infant numerical abilities are related to mathematical abilities later in childhood. Here, we provide evidence that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
272
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(314 citation statements)
references
References 39 publications
15
272
3
8
Order By: Relevance
“…Therefore, the registration of early arithmetic skills and the development of number sense is a strong measure to predict later achievement in the arithmetic field. Children that already handle quantities quite well show better performances in mathematic tasks later on compared to other children of the same age (Starr, Libertus, & Brannon, 2013).…”
Section: Importance Of Early Arithmetic Skills and Later Mathematicalmentioning
confidence: 99%
“…Therefore, the registration of early arithmetic skills and the development of number sense is a strong measure to predict later achievement in the arithmetic field. Children that already handle quantities quite well show better performances in mathematic tasks later on compared to other children of the same age (Starr, Libertus, & Brannon, 2013).…”
Section: Importance Of Early Arithmetic Skills and Later Mathematicalmentioning
confidence: 99%
“…Evidence for this idea includes the fact that ANS acuity of typical school-and preschool-aged children have been found positively correlated with their actual and future math skills (Anobile, Stievano, & Burr, 2013;Chen & Li, 2014;Halberda, Mazzocco, & Feigenson, 2008;Libertus, Feigenson, & Halberda, 2011, 2013Pinheiro-Chagas et al, 2014;Starr, Libertus, & Brannon, 2013) -but see also (Lyons, Price, Vaessen, Blomert, & Ansari, 2014;Sasanguie, Defever, Maertens, & Reynvoet, 2014). Furthermore, dyscalculic children have often been found to have poorer numerosity thresholds (Mazzocco, Feigenson, & Halberda, 2011;Piazza et al, 2010) -but see also Rousselle and Noel (2007) for a different account.…”
Section: Items Connection Affects Ans and Texture-density 140mentioning
confidence: 99%
“…In both cases, action tasks and attention tasks point to the same underlying competence, supporting the validity of each method. Finally, a number of recent publications have demonstrated that individual differences in infants' attentional responding during infancy correlate with performance in more active paradigms, both within the infancy period [Thoermer, Woodward, Sodian, Perst, & Kristen, 2013], and when children are in preschool [Starr, Libertus, & Brannon, 2013;Wellman, Lopez-Duran, LaBounty, & Hamilton, 2008;Wellman, Phillips, Dunphy-Lelii, & LaLonde, 2004;Yamaguchi, Kuhlmeier, Wynn, & vanMarle, 2009; see also Halberda, Mazzocco, & Feigenson, 2008]. These relationships suggest that infancy methods are tapping actual cognitive processing of the level attributed to them by CK researchers.…”
mentioning
confidence: 99%